Effect of freezing rate and storage on the rheological, thermal and structural properties of frozen wheat dough starch. (29th March 2016) - Silvas‐García, María Irene; Ramírez‐Wong, Benjamín; Torres‐Chávez, Patricia Isabel; Bello‐Pérez, Luis Arturo; Carvajal‐Millán, Elizabeth; Barrón‐Hoyos, Jesús Manuel; Rodríguez‐García, Mario Enrique; Vázquez‐Lara, Francisco; Quintero‐Ramos, Armando
Abstract : The aim of this study was to evaluate the effects of freezing rate and storage time on the properties of frozen wheat dough starch. The dough was frozen at either slow (−0.14°C/min) or fast (−1.75°C/min) rates and stored at −20°C for 8 weeks. Every 2 weeks, the frozen dough was sampled and freeze‐dried. Analyses of the dried dough included damaged starch, paste properties, and thermal, morphological, and structural properties. Damaged starch increased significantly during storage, and it was higher in the dough frozen at a slow rate than in the dough frozen at a fast rate. The peak viscosity during storage gradually but significantly decreased. During this period, the peak viscosity was higher for the dough frozen at a slow rate than the dough frozen at a fast rate. The enthalpy of starch crystallite fusion gradually but significantly increased during storage, and it was lower in the dough frozen at a slow rate than in the dough frozen at a fast rate. The structural properties show a decrease in the crystalline percent as a result of the freezing and storage time. SEM images show that starch granules were separated from the gluten matrix after storage, and separation was greater for the dough frozen at a fast rate than that frozen at a slow rate. The freezing rate and storage time increased starch damage and changed the microstructure of the dough.